Business model adaptation in the male grooming industry during international market entry: a comparative analysis of Ukraine and the United States - Kyseliuk, Rostyslav (Академічні візії, 2026)
The entry of men’s grooming industry enterprises into foreign markets requires scientifically based coordination of the service format with local demand and institutional conditions, since the direct transfer of home practice does not guarantee either value for the client in the form of a predictable result and safe service or economic value for the enterprise. The purpose of the study is to develop a three-level framework for adapting the business model of a Ukrainian men’s grooming enterprise to the US market and operationalize it in a comparative matrix of 10 components. A structured integrative review was used to systematize theoretical approaches; comparative management analysis was used to establish differences between the two countries’ conditions; thematic coding and matrix synthesis were used to identify group factors. The empirical basis consisted of 23 scientific and official sources from the Scopus, Web of Science Core Collection, EBSCO Business Source Complete, and Google Scholar databases, as well as materials from the Organization for Economic Cooperation and Development, the State Statistics Service of Ukraine, the Executive Office of the President of the United States, and the Bureau of Labor Statistics of the United States. The developed framework delineates the model’s stable core, market localization and institutional fit. It has been established that the stable core includes the service result agreed with the client, the technical quality of its execution, the sanitary safety of the workplace and tools, professional consultation, consistent brand promise and the systematic transfer of knowledge to the staff. It is shown that customer segmentation, service menu, prices, attractions and booking channels, location format, terms of employment and partner network need to be assessed for a specific local segment. Registration, tax, licensing, labor, health, insurance, information and infrastructure requirements must be met by the company and professionals before entering into irrevocable commitments in the selected US state and city. For the first time, the simultaneous assessment of adaptation solutions based on their reversibility and the binding nature of related legal requirements is substantiated for the researched area. The practical significance of the results lies in the possibility for barbershop owners and managers to use the matrix to audit readiness, choose a jurisdiction, design a legal pilot, and decide whether to continue, adjust, or stop scaling. Within the proposed framework, digital tools can be applied for booking, consent capture, repeat demand analysis and consultation support to implement and monitor adaptation solutions.